2022
DOI: 10.1186/s12879-022-07165-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical risk factors related to severe COVID-19 in Iran: a multi-center study

Abstract: Background Iran was one of the first countries to be affected by COVID-19. Identifying factors associated with the severity of COVID-19 is effective in disease management. This study investigated the epidemiological and clinical features and factors related to the severity of COVID-19 in one of the less privileged areas in Iran. Methods In a multi-center study, all patients admitted to Zahedan University of Medical Sciences hospitals in southeaster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…These studies together with ours, point in another direction than the many studies nding a higher prevalence of SARS-CoV-2, more severe morbidity and greater mortality related to the disease among PWUD (12)(13)(14)(15). Strathdee and colleagues found a prevalence of SARS-CoV-2 among PWUD in the San Diego-Tijuana border to be higher than estimates from the general population in either city (32,33).…”
Section: Discussionsupporting
confidence: 58%
“…These studies together with ours, point in another direction than the many studies nding a higher prevalence of SARS-CoV-2, more severe morbidity and greater mortality related to the disease among PWUD (12)(13)(14)(15). Strathdee and colleagues found a prevalence of SARS-CoV-2 among PWUD in the San Diego-Tijuana border to be higher than estimates from the general population in either city (32,33).…”
Section: Discussionsupporting
confidence: 58%
“…Then, a smoking habit was an independent risk factor for slowing the duration of recovery from long COVID (Table 5), suggesting a need for increased attention to smoking during the whole clinical course of COVID‐19. On the other hand, sex (female), older age, and the presence of comorbidities were not independent risk factors for prolonged recovery in the analysis (Table 5), although several previous studies presented their negative effects on COVID‐19 10,12,26,36,40–43 . Of course, this finding must be confirmed in further studies; however, a prominent result was that smoking exerts a crucial effect on these infectious problems.…”
Section: Discussionmentioning
confidence: 78%
“…After deleting duplicates, we identified 2463 studies from four databases and then screened articles by title and full text according to the study's objectives. Finally, 69 studies were included in the meta-analysis (Figure 1), of which 62 studies had assessed risk factors for death from COVID ); 13 studies determined risk factors for severity (( 41,50,[53][54][55]65,[90][91][92][93][94][95][96] ), out of which six studies reported both outcomes ( (35,44,(47)(48)(49)59)). Out of 69 studies, 33 were cohort studies, eight were case-control studies, and 28 were cross-sectional studies.…”
Section: Search Results and Quality Assessmentmentioning
confidence: 99%